2003
DOI: 10.1300/j017v21n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electronic Discussion Forums in Social Work Diversity Education: A Comparison of Anonymous and Identified Participation

Abstract: Two Web-based forums for discussing diversity issues were evaluated as part of graduate social work education. Data included surveys from 91 students as well as aggregate Web use information. Outcomes included perceived learning benefits related to cultural competency, improved relationships and benefits of anonymous vs. identified participation in the forums. We found that (1) 75% of the students reported benefits related to learning cultural competency; (2) just over 60% experienced positive impacts on relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
2
23
3
Order By: Relevance
“…We also observed that when there is anonymity, participants tend to post notes that attain an in depth level of critical thinking . One possible legitimate concern that instructors may have about the use of anonymity is the occurrence of aggressive and malicious behaviour such as flaming (Bertera & Littlefield, 2003). However, we found no evidence for this in our earlier study .…”
Section: Comments and Lessons Learned From Both Blended Modelscontrasting
confidence: 84%
“…We also observed that when there is anonymity, participants tend to post notes that attain an in depth level of critical thinking . One possible legitimate concern that instructors may have about the use of anonymity is the occurrence of aggressive and malicious behaviour such as flaming (Bertera & Littlefield, 2003). However, we found no evidence for this in our earlier study .…”
Section: Comments and Lessons Learned From Both Blended Modelscontrasting
confidence: 84%
“…In line with the findings of Bertera and Littlefield (2003), some students alluded to the sense of community online forums created, for example, 'great, loved reading others' and 'good to see additional points of view'. One student commented verbally, that she had never felt so well supported within a group, which may have resulted from a possible 'knock on' effect of using online forums (Ertmer, Richardson et al 2010).…”
Section: Tablesupporting
confidence: 63%
“…Students are able to access Elearning materials anyplace and anytime controlling the pace at which they progress (Blass and Davis 2003;Casquero, Portillo et al 2010). Issues which might either be time consuming or of a sensitive nature can be explored in a more neutral environment, giving students more autonomy and time to consider and reflect (McFerrin 1999;Schoech 2000;Bertera and Littlefield 2003). VLEs help build a sense of community for both students and staff (Clarke and Abbott 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of an anonymous electronic forum proved beneficial for bachelors of social work (BSW) students enrolled in a diversity course as students reported positive regard for the forum and reported that the anonymity of the forum allowed them to express themselves openly, without fear of being attacked (Huff & Edwards, 2001). Similar results on selfreported gains have been found when using online technology within MSW courses on diversity (Bertera & Littlefield, 2003;Lee & Bertera, 2007). In a similar study, nearly three-quarters of MSW students felt that the forum allowed them to ask questions or make comments that they would not have felt comfortable saying in class, and two-thirds of students reported that the forum was useful for discussing sensitive issues (Van Soest et al, 2000).…”
Section: Use Of Instructional Technology In Multicultural Educationmentioning
confidence: 71%